Teaching for Values in Human–Computer Interaction - Eriksson, Eva; Nilsson, Elisabet M.; Hansen, Anne-Marie; Bekker, Tilde (Frontiers in Computer Science, 2022)
There is an increasing awareness of the importance of considering values in the design of technology. There are several research approaches focused on this, such as e.g. value-sensitive design, value-centred human-computer interaction (HCI), and value-led participatory design, just to mention a few. However, less attention has been given to developing educational materials for the role that values play in HCI, why hands-on teaching activities are insufficient, and especially teaching activities that cover the full design process. In this paper we claim that teaching for ethics and values in HCI is not only important in some parts of the design and development process, but equally important all through. We will demonstrate this by a unique collection of 28 challenges identified throughout the design process, accompanied by inspirational suggestions for teaching activities to tackle these challenges. The paper is based on results from applying a modified pedagogical design pattern approach in the iterative development of an open educational resource containing teaching and assessment activities and pedagogical framework, and from pilot testing. Preliminary results from pilots of parts of the teaching activities indicate that student participants experience achieving knowledge about how to understand and act ethically on human values in design, and teachers experience an increased capacity to teach for values in design in relevant and innovative ways. Hopefully, this overview of challenges and inspirational teaching activities focused on values in the design of technology can be one way to provide teachers with inspiration to sensitize their students and make them better prepared to become responsible designers by learning how to address and work with values in HCI.